Clinical Supervision to Improve the Ability of Class V Teachers Elementary School deep Cooperative Learning Model - Kamat Kamat (SEMAR Journal : Educations Studies, 2020)
This research reveals the teacher's low ability in preparing Classroom Action Research Proposals (CAR). This proved to be the absence of teachers who submitted classroom action research proposals in the last 2 years. This study aims to determine the extent of the effectiveness of the application of group guidance in an effort to improve teacher competence in the preparation of CAR proposals. This research was carried out in the guiding process at the regular meeting of Subject Teachers at Neger 06 Seluma Middle School. The School Action Research is conducted in two cycles, where each cycle has four stages, namely planning, implementation, observation and reflection. The results in the study are: 1). The indicator of success in the study is: if 10% of the number of coaching participants have obtained an average value of ≥ 85, 2). cycle II obtained supervisor observation data (4.22), teacher observation (4.14), classical work results (84.02). Indicators of success have exceeded School Action Research declared successful. 3). Very effective group guidance in an effort to improve competency in the preparation of CAR proposals reaching 90% of the total number of participants has succeeded in developing CAR proposals as expected.Keywords: Group Guidance, competence, CAR